Paths and Implications of Indo-Russian Arctic Cooperation from the Perspective of India’s Arctic Policy - Jinshan Yang (Studies in Law and Justice, 2024)
India’s earliest involvement in the Arctic was influenced by the Antarctic, driven primarily by the need for scientific research on the environment and climate change. Later, the importance of Arctic energy and geo-strategic factors became more and more prominent, and these three factors are now the core drivers of India’s involvement in the Arctic. Depending on the degree of importance and involvement of the Indian government in Arctic affairs at different times, India’s Arctic policy can be categorized into three stages: the unformed stage (before 2007), the embryonic stage (2007-2012), and the initial stage (2012-present). With the gradual molding of India’s Arctic strategy, Indo-Russian Arctic cooperation has gradually become a hot topic. Specific cooperation paths include energy, scientific research, transportation and other fields. The driving force of Indo-Russian Arctic cooperation includes historical cooperation foundation, objective cooperation needs, geopolitical strategy and other factors, but at the same time, India’s domestic disagreement on Arctic policy, its own economic level, the complex situation in South Asia, the international political situation, economic risks, technical difficulties, and the U.S.-Russian rivalry also limit the deepening of Indo-Russian Arctic cooperation. For China, India-Russia Arctic cooperation in Arctic affairs and geopolitics in the short term will not pose too much of a threat, but from the point of view of prevention, should still be India and Russia to join forces to maintain appropriate vigilance, in order to better safeguard national interests.